Statistical Meso-Mechanics of Damage and Failure : How Microdamage Induces Disaster : Series Publication of Multiscale Mechanics /: How Microdamage Induces Disaster : Series Publication of Multiscale Mechanics. (2019) - Unknown
No abstract available